Molecular pathogenesis of Alzheimer's disease onset in a mouse model: effects of cannabidiol treatment - Bishara, Mary A.; Chum, Phoebe P.; Miot, Fritz E. L.; Hooda, Ankita; Hartman, Richard E.; Behringer, Erik J. (Frontiers in Neuroscience, 2025)
IntroductionAlzheimer's disease (AD) is a common neurodegenerative condition involving a complex blend of disturbances in synaptic development and maintenance, neurovascular cross-talk, ionic and nutrient transport, and mitochondrial metabolism. The precise molecular profile of AD onset with insight for major pathological contributors remains unclear with corresponding impedances in therapeutic development. The current study sought two objectives, as (i) to resolve the molecular pathogenesis from cognitive impairment to the onset of AD-like neuropathology and (ii) whether the novel agent cannabidiol (CBD), noted for its neuroprotective effects, influences the molecular transition associated with AD onset.MethodsDietary CBD was administered daily (80–100 mg/kg/day) in male 3xTg-AD mice and wild-type B6129SF2/J animals from 4.5 to 6.5 mo of age with inclusion of vehicle controls. RNA sequencing encompassed longitudinal and cross-sectional blood and brain samples, respectively. Metabolomics and behavioral analyses examined brain regions (cortex, hippocampus) and associated integrated neurocircuitry.Results and discussionThere were >1,000 differentially expressed markers of AD onset, whereby >75% were either eliminated or reversed in the direction of expression in response to CBD. Signaling pathways encompassed synaptic development and plasticity (e.g., Foxp2), neurovascular interactions (Smad9, Angptl6), receptors and ion channels (Gria4, Chrna2, Rgs7/Rgs7bp), mitochondrial genes (Ndufa7, Cox7a2), immunity (Ncr1), oxidation-reduction (Esr1), lipid synthesis (Fasn, ApoE), and carbohydrate metabolism (Mafa, Mlxipl). As potentially addressable with CBD treatment, AD onset represents molecular integration of neurovascular interactions, channelopathies, metabolic disturbances, and aberrations in developmental genes with involvement of major pathological contributors such as inflammation, oxidative signaling, dyslipidemia, and insulin resistance.